ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Eko Rahayu, 12.05.52.0081; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2016)
The study examine the effect of current ratio, net working capital to total assets ratio, return on equity, net profit margin, debt to equity ratio, total assets turnover and firm size on financial distress. This study used 169 mining companies as population listed on Indonesia Stock Exchange for the period 2009-2013. The sampling method used purposive sampling resulting in a total sample of 68 mining companies. Relationship and (or) influence between variable is described by using multiple regression analysis.Â The result showed that the current ratio and net profit margin have positive effect and significant to the financial distress. Return on equity and total asset turnover have negative effect and significant to the financial distress. Net working capital to total asset and debt to equity ratio have negatif effect and no significant to the financial distress.Whereas firm size have positif effect and no significant to the financial distress.Keywords:Â Current Ratio, Net Working Capital To Total Asset, Return On Equity, Net Profit Margin, Total Asset Turnover, Firm Size, Financial Distress